2014
DOI: 10.1021/la503331r
|View full text |Cite
|
Sign up to set email alerts
|

Systematical Characterization of Phase Behaviors and Membrane Properties of Fatty Acid/Didecyldimethylammonium Bromide Vesicles

Abstract: Fatty acids (FAs) are known to form vesicle structures, depending on the surrounding pH conditions. In this study, we prepared vesicles by mixing FAs and a cationic surfactant, and then investigated their physicochemical properties using fluorescence spectroscopy and dielectric dispersion analysis (DDA). The assemblies formed from oleic acid (OA) and linoleic acid (LA) were modified by adding didecyldimethylammonium bromide (DDAB). The phase state of FA/DDAB mixtures was investigated with pH titration curves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…Previous studies have shown that the apparent pKa of oleic acid in different surfactant and lipid mixtures ranges from 6.0 to 9.5. For example, the pKa of pure oleic acid vesicles is 8.0- 9.5 [27,42,43]. While when mixed with monoolein, the pKa was 6.0-7.0 [24].…”
Section: Dissociation Of Oleic Acid In Mixed 7:3 Dppc-oleic Acid Membmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the apparent pKa of oleic acid in different surfactant and lipid mixtures ranges from 6.0 to 9.5. For example, the pKa of pure oleic acid vesicles is 8.0- 9.5 [27,42,43]. While when mixed with monoolein, the pKa was 6.0-7.0 [24].…”
Section: Dissociation Of Oleic Acid In Mixed 7:3 Dppc-oleic Acid Membmentioning
confidence: 99%
“…The pKa of an isolated carboxyl group in water is~4.8 [23], while the apparent pKa of oleic acid's carboxyl headgroup tends to be higher depending on the type of co-existing molecules in the mixture and structure of the assembly (i.e., pKa of~6.1 in the hexagonal phase of oleic acid and monoolein mixtures [24]; pKa of~6.5 in 4:6 oleic acid-DPPE vesicles [25]; pKa of~8.0-8.5 in pure oleic acid vesicles [23]; and, an even higher pKa of~9.85 for oleic acid monolayers at air-water interface [26]). The deprotonation of oleic acid in the system consequently alters molecular level lateral interactions and phase behavior of the mixture [23,27]. Likewise, deprotonation would significantly impact the interaction between membranes and oleic acid can be used to induce pH-dependent membrane fusion or membrane repulsion in model systems [25,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of these bilayered vesicles was investigated through a simple technique: the titration of clear micellar solutions of alkaline salts with acids (usually inorganic acids such as HCl) [1,2,4,5,6,7,8]. The concentration of undissociated acid increases with acid quantity (RCOOH), and the initial transparent layout becomes opaque due to the formation of a vesicular supra-molecular structure [4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of undissociated acid increases with acid quantity (RCOOH), and the initial transparent layout becomes opaque due to the formation of a vesicular supra-molecular structure [4,5,6,7,8]. The dispersion’s pH [4,5,6,7,8], the 13 C Nuclear Magnetic Resonance (NMR) signals [7], and the X-ray diffraction peaks [8] are modified due to vesicle formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation